2020
DOI: 10.2147/ott.s237307
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circ_0058124 Upregulates MAPK1 Expression to Promote Proliferation, Metastasis and Metabolic Abilities in Thyroid Cancer Through Sponging miR-940</p>

Abstract: Background: Thyroid cancer (TC) is an endocrine disease, and its progression is regulated by many factors, including circular RNAs (circRNAs). However, as a new circRNA, the role of circ_0058124 in TC is worth further exploration. Methods: The expression levels of circ_0058124, microRNA-940 (miR-940) and mitogen-activated protein kinase 1 (MAPK1) were assessed by quantitative polymerase chain reaction (q-PCR). The circular characteristic of circ_0058124 was identified by oligo (dT) 18 primers, Ribonuclease R (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
(31 reference statements)
2
21
0
Order By: Relevance
“…This new area of research is extra attractive for their applications in clinical practice as tumor marker or molecular therapeutic targets are possible (24)(25)(26). In a few available studies, circRNAs are reported to play the role of oncogene or tumor suppressor gene, affecting the occurrence of tumors development, such as lung squamous cell carcinoma, colorectal cancer, hepatocellular carcinoma, thyroid cancer, and so on (27)(28)(29)(30). However, there have been little studies on circRNAs in gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…This new area of research is extra attractive for their applications in clinical practice as tumor marker or molecular therapeutic targets are possible (24)(25)(26). In a few available studies, circRNAs are reported to play the role of oncogene or tumor suppressor gene, affecting the occurrence of tumors development, such as lung squamous cell carcinoma, colorectal cancer, hepatocellular carcinoma, thyroid cancer, and so on (27)(28)(29)(30). However, there have been little studies on circRNAs in gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In a more refined analysis, the miRWalk databases were used to determine validated targets miR-106b-5p genes involved in gastric carcinogenesis and 14 genes from this pathway were found: APC (regulator of the WNT signaling pathway), CCND1 (cyclin D1) CDKN1A (cyclin-dependent kinase inhibitor 1), E2F1, E2F2, E2F3 (transcription factor 1, 2, and 3, respectively), FZD9 (frizzled class receptor 9), MAPK1 (mitogen-activated protein kinase 1), MYC (proto-oncogene BHLH transcription factor), RB1 (transcriptional corepressor 1), SMAD4 (SMAD family member 4), TCF7L2 (transcription factor 7-like 2), TGFBR2 (transforming growth factor β receptor 2), and TP53 (tumor protein p53). Considering the main functions described in the process of carcinogenesis, these genes are involved in cell cycle regulation and tumor progression, cell growth, adhesion and migration, proliferation, differentiation, genome stability, DNA repair, and apoptosis [42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The identi ed DEmiR and DEGs have not been reported in the previous study related to the pathogenesis of neuropathic pain. MiR-940 is mainly related to proliferation and metastasis of cancer, such as gastric cancer (11), endometrial carcinoma (12), thyroid cancer (13), and cervical cancer (14). Interestingly, miR-940 also regulates the in ammatory response in osteoarthritis (OA) (15) and spinal cord injury (16).…”
Section: Discussionmentioning
confidence: 99%